BEYOND HATEWARE: AFFECT, NETWORKS, AND COLLABORATIVE ECOSYSTEMS IN A FANDOM DISCORD SERVER - Margheim, Nicole Anne (AoIR Selected Papers of Internet Research, 2026)
Academic attention on Discord has often focused on its potential for harassment and spreading hate and bigotry, at time even called "hateware" (Brown and Hennis 2019). As the user base of Discord expands beyond gamers and more internet groups, such as media fandoms, take up the platform, there has been increased scholarship examining how these new groups of users engage with Discord in more positive ways. This paper examines how one such server, a private 2 fanfiction Discord server called The Lagoon, is maintained through the relations between its members. Using distributed cognition and Actor Network Theory (ANT), this paper investigates relations between users in The Lagoon through digital ethnography, including three months of participant observation, semi-structured interviews with 26 members, and ongoing conversations with server administrators. Unlike prior studies that focus on large, highly active servers, this research explores a smaller, more intimate server of approximately 125 members, reflecting the size and structure of most Discord servers. Findings reveal a complex, unevenly distributed network where active members engage in daily discussions, collaborative writing, and interactive “bot” usage, while the less active members still report feeling the affect generated by those interactions. This paper introduces the concept of the “collaborative ecosystem” to capture these messy relations, proposing that cognitive processes like inspiration and productivity are distributed throughout the ecosystem. While acknowledging potential imbalances and toxicity, this study highlights the capacity for positive collaboration on Discord, adding to recent scholarship that analyses the platform beyond its potential for "hateware."